PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK MENINGKATKAN PEMAHAMAN MORAL PADA PEMBELAJARAN PKN SISWA KELAS V SDN KUTA PASIE - Raudatin; Musdiani; Raziska Ibrahimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low moral understanding of elementary school students, marked by cases of bullying and student fights. This condition is worsened by conventional learning methods and minimal use of technology-based media, so moral values in Civic Education (PKN) are not fully understood. This study aims to: (1) describe the development process of animated video learning media on norms in life, and (2) determine its effectiveness in improving moral understanding of fifth-grade students at SDN Kuta Pasie. This research uses Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving 21 fifth-grade students as a saturated sample. The animated video was developed using Canva and validated by material and media experts. Results showed combined validity of 95.415% (Very Valid), practicality of 90% (Very Practical), and significant learning improvement with average scores increasing from 47.62 (pretest) to 82.38 (posttest), with 90.47% class completion rate. It is concluded that the animated video learning media is feasible, practical, and effective in improving students' moral understanding of norms in life in Civics learning at class V SDN Kuta Pasie.